Sistematik Literatur Review: Pengaruh Keselamatan dan Kesehatan Kerja (K3) terhadap Kinerja Karyawan di Industri Manufaktur - Tira, Rika Iyut; Nasution, Istifani; Apriani, Elisa; Hasibuan, Abdurrozzaq (Lembaga Yasin AlSys, 2025)
Occupational health and safety (OHS) is a critical aspect of the manufacturing industry, which is characterized by high work-related risks, as it plays a vital role in protecting employees from workplace accidents and occupational diseases. This study aims to systematically analyze the impact of OHS implementation on employee performance in the manufacturing sector. A quantitative approach was employed, with a literature review as the primary data collection strategy, conducted through the search and selection of relevant and verified scientific articles from databases such as Google Scholar, JSTOR, and ProQuest. The findings indicate that OHS implementation—which includes a safe work environment, the use of standard-compliant equipment, and adherence to safety procedures—has a significantly positive impact on employee performance. A safe workplace has been shown to enhance productivity, efficiency, and work motivation. The conclusion of this study affirms that implementing an OHS system is not only a legal obligation but also an essential strategy for developing a healthy, safe, and high-performing workforce in the manufacturing sector. These findings reinforce the position of OHS as the foundation of a productive, disciplined, and results-oriented work culture, ultimately contributing to industrial competitiveness.